2006
DOI: 10.1002/sres.754
|View full text |Cite
|
Sign up to set email alerts
|

Theory and practice of systems methodology in ERP implementation

Abstract: The application and evolution of MRP II/ERP can be roughly divided into three stages: the introduction stage, the growth stage, and the maturity stage. A successful ERP implementation requires knowledge on both ERP systems and business management. In implementing ERP, the business processes of those enterprises adopted ERP systems need to be examined. It is important to understand the ERP system itself and the business processes involved with the ERP systems and the enterprises-adopted ERP systems. In order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Analysing commonly applied strategies, Mabert et al (2003) recommend following several factors during implementation, which are considered essential in order to enhance the understanding of the procedures required (Table IV). Beheshti (2006) propose an implementation strategy based on the one-time complete conversion from an old legacy system to new ERP system, which is similar to Zhang and Li's (2006) complete conversion. Another proposed implementation method is the gradual replacement of legacy programme with ERP system.…”
Section: Abidnourmentioning
confidence: 99%
“…Analysing commonly applied strategies, Mabert et al (2003) recommend following several factors during implementation, which are considered essential in order to enhance the understanding of the procedures required (Table IV). Beheshti (2006) propose an implementation strategy based on the one-time complete conversion from an old legacy system to new ERP system, which is similar to Zhang and Li's (2006) complete conversion. Another proposed implementation method is the gradual replacement of legacy programme with ERP system.…”
Section: Abidnourmentioning
confidence: 99%
“…The system is integrated through standard business processes and includes all the data and information (Jigeesh, ). To reach better work efficiency, ERP needs to simplify the business processes as a functional unit and integrated system (Zhang and Li, ; Sahran et al ., ). Nieuwenhuyse et al .…”
Section: Literature Reviewmentioning
confidence: 97%
“…The system is integrated through standard business processes and includes all the data and information (Jigeesh, 2011). To reach better work efficiency, ERP needs to simplify the business processes as a functional unit and integrated system (Zhang and Li, 2006;Sahran et al, 2010). Nieuwenhuyse et al (2011) indicated that ERP integrates the functions of finance, manufacturing and human resources and can assist in the planning and integration of information using information technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…ERP systems can be defined as a suite of software modules that allows an organization to automate and integrate the majority of its business functions by sharing common data and business processes across the enterprise (Davenport, 1998;Klaus et al, 2000;Zhang and Li, 2006;Jacobs and Weston, 2007) and across entire supply chains (Davenport and Brooks, 2004). ERP systems have been associated with a wide range of benefits including; reduced order cycle time, reduced stock holding, real-time management information and improved customer service (Shang and Seddon, 2002;Nah et al, 2003).…”
Section: 1erp Adoption Literaturementioning
confidence: 99%